2020
DOI: 10.3233/jad-191212
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Early Stage Alzheimer’s Disease in the United States: Cross-Sectional Analysis of a Prospective Cohort Study (GERAS-US)1

Abstract: Background: Costs associated with early stages of Alzheimer's disease (AD; mild cognitive impairment [MCI] and mild dementia [MILD]) are understudied. Objective: To compare costs associated with MCI and MILD due to AD in the United States. Methods: Data included baseline patient/study partner medical history, healthcare resource utilization, and outcome assessments as part of a prospective cohort study. Direct, indirect, and total societal costs were derived by applying standardized unit costs to resources for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 38 publications
2
76
1
Order By: Relevance
“…This review identified few studies evaluating the broader economic burden of MCI likely due to AD, probably because of the recent introduction of this term and the difficulty to establish this diagnosis (57). These studies demonstrated that individuals with MCI likely due to AD require social care and informal care more than their age-matched peers; and that this is further increased in those with mild AD dementia (32,45). A similar trend is seen with caregiver health care costs when they are included in the estimation of total costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review identified few studies evaluating the broader economic burden of MCI likely due to AD, probably because of the recent introduction of this term and the difficulty to establish this diagnosis (57). These studies demonstrated that individuals with MCI likely due to AD require social care and informal care more than their age-matched peers; and that this is further increased in those with mild AD dementia (32,45). A similar trend is seen with caregiver health care costs when they are included in the estimation of total costs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that, compared to MCI, significantly more individuals with mild AD were pushed to an income below the federal poverty level. Patients' employment rates were found to significantly drop from 21.4% to 9.4%; and the number of employed adults who reduced their work significantly rose from 3.2% to 13.8% (32). In the broader AD population, a significant relationship between dependency and household income has not been found (44).…”
Section: Impact Of Ad On Other Socioeconomic Aspectsmentioning
confidence: 91%
See 2 more Smart Citations
“…A recent literature review of multinational studies found that informal care costs represent approximately 60% of total costs for patients with early stages of AD, increasing to 72.5% for patients with severe AD [32]. Although cognitive function has been identified as the main driver of societal costs of patients with AD [33], both cognitive decline and physical disability were found to be predictors of increased informal care costs [34]. Moreover, the need for social and informal care is already higher in patients with mild cognitive impairment likely due to AD than age-matched controls and increasing further in patients with AD dementia [32].…”
Section: Accepted Manuscript 1) Do Qalys Undervalue Treatments For Older Patients?mentioning
confidence: 99%